Malignant pancreatic serous cystic neoplasms: systematic review with a new case. Issue 1 (December 2016) - Huh, Jimi; Byun, Jae; Hong, Seung-Mo; Kim, Kyung; Kim, Jin; Lee, Seung; Kim, Hyoung; Lee, Moon-Gyu
Abstract Background This study analyzes the clinicopathologic and radiologic characteristics of malignant serous cystic neoplasm (SCN) of the pancreas through systematic review and an institutional case report. Methods A comprehensive literature search was performed in the MEDLINE database to identify studies on malignant SCNs of the pancreas that had detailed clinicopathologic and radiologic information. A computerized systematic search of our institutional database was also performed to identify cases of malignant SCN for addition to the systematic review. Using the final included cases, we analyzed the clinicopathologic and radiologic features of malignant SCNs of the pancreas. Results A review of 136 candidate articles identified 26 studies with 26 cases that had detailed clinical information. Our institutional data search added one case. The systematic review of the 27 cases revealed that primary tumors (mean diameter 10.2 ± 4.0 cm) mainly involved the body and tail of the pancreas (n  = 16) and frequently invaded adjacent organs (n  = 19). Distant metastases occurred in 14 patients (synchronous, n  = 5; metachronous, n  = 8; both, n  = 1), most commonly in the liver (n  = 13). Imaging features of malignant SCNs of the pancreas were identical to the benign counterpart, except local invasion or distant metastases. The prognosis was excellent in that 17 were alive at the time of writing with a median follow-up period of 2 years. Conclusions The malignant potential of SCNs of the pancreas should be considered in the diagnosis and management of patients with pancreatic SCNs.